Impoliteness Strategies in Efl Context: Teacher – Student Interaction in English for Specific Purposes (Esp) Class - Eko Suwignyo; Dwi Rukmini; Rudi Hartono; Hendi Pratama (Universitas Negeri Semarang, 2022)
The impoliteness can happen in various fields of human life including in the classroom interaction. This study aims to describe the impoliteness strategies used by the teacher and the learners in doing interaction. The data was taken from the teacher and students interaction in English for specific purposes class at ABS school. Then, the data was analyzed using Culpeper’s taxonomy (1996). The result shows that bald on record strategy was the most frequently used either by the teacher or students in doing interaction. There was also other strategies such as positive impoliteness, negative impoliteness, and off record impoliteness. Beside that, the data also shows some responses to the impoliteness such as accepting and countering to the impoliteness. Therefore, the result of this study will be beneficial for the material designer, teachers and also students as references to avoid the impolite act and use the polite ones in doing interaction.